2014
DOI: 10.1097/sap.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

Breast Augmentation With Autologous Fat Injection

Abstract: IntroductionAutologous fat transplantation has attracted great interest in breast augmentation for cosmetic purpose. In the present study, we reported our experience in fat grafting in breast in 105 cases, and some detailed procedure concerning efficacy and safety of grafting was evaluated.MethodsFat was harvested using 20-mL syringe attached to a 3-hole blunt cannula in a diameter not beyond 3 mm. After washing with cool normal saline to remove blood, the fat was managed with open method using cotton towel as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 25 publications
0
52
0
1
Order By: Relevance
“…54,[56][57][58] Although various surgical procedures have been described for improving survival of fat grafts, including washing, 36,61,62 centrifugation, 27,63-65 decantation, 61 and not washing, 66 there is still controversy about their esthetic outcome, complications, and long-term results. 36,54,[56][57][58] Coleman and Saboeiro 27 introduced the structural fat grafting technique and emphasized the importance of removing nonviable aspirate components, such as oil and blood cells by centrifugation. 65 Following the initial description, Coleman's technique has been popularized; it also emphasizes an atraumatic method of fat harvesting, centrifugation, and, especially, a small amount of fat injection in order to provide maximal contact Primary and Secondary Breast Augmentation between fat and the recipient tissue.…”
Section: Autologous Fat Graftingmentioning
confidence: 99%
See 2 more Smart Citations
“…54,[56][57][58] Although various surgical procedures have been described for improving survival of fat grafts, including washing, 36,61,62 centrifugation, 27,63-65 decantation, 61 and not washing, 66 there is still controversy about their esthetic outcome, complications, and long-term results. 36,54,[56][57][58] Coleman and Saboeiro 27 introduced the structural fat grafting technique and emphasized the importance of removing nonviable aspirate components, such as oil and blood cells by centrifugation. 65 Following the initial description, Coleman's technique has been popularized; it also emphasizes an atraumatic method of fat harvesting, centrifugation, and, especially, a small amount of fat injection in order to provide maximal contact Primary and Secondary Breast Augmentation between fat and the recipient tissue.…”
Section: Autologous Fat Graftingmentioning
confidence: 99%
“…In fact, there are numerous clinical studies that corroborate esthetic outcome and patient satisfaction. [26][27][28][29][30][31][32][33][34][35][36]54,[56][57][58] First introduced by Bircoll 23,24 in the 1980s for esthetic breast surgery, autologous fat grafting had the major advantage of autologous tissue transplantation in terms of natural and long-term results, even when secondary and tertiary surgical sessions were necessary. However, at that time, the American Society of Plastic and Reconstructive Surgery (ASPRS) Ad Hoc Committee on New Procedures concluded that the potential scarring and calcifications could interfere with diagnosis of breast cancer.…”
Section: Autologous Fat Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few alternative methods for a patient who is not satisfied with the size and form of the implant but does not want repeated surgery to remove the existing implant and re-implant a different one, or has experienced difficulty with an autologous fat graft due to a thin body [2]. Therefore, the authors of this paper report that relatively satisfactory results using a filler to improve the size and shape of the implant that has already been inserted into the breast.…”
Section: Introductionmentioning
confidence: 76%
“…Even though revision using an autologous fat graft has been attempted, implanted fat absorption and a sacrificed donor site are disadvantages, requiring repetitive procedures [2,3]. There are few alternative methods for a patient who is not satisfied with the size and form of the implant but does not want repeated surgery to remove the existing implant and re-implant a different one, or has experienced difficulty with an autologous fat graft due to a thin body [2].…”
Section: Introductionmentioning
confidence: 99%